Analysis of Asiaticoside in Beagle Dog Plasma by Liquid Chromatography/ Electrospray Ionization Tandem Mass Spectrometry and its Application to Pharmacokinetic Studies - Liu, Shijia; Ju, Wenzheng; Zhou, Ling; Liu, Zixiu; Li, Changyin; Chen, Min; Zhang, Jun; Tan, Hengshan (Current Pharmaceutical Analysis, 2011)
A rapid and sensitive liquid chromatography/tandem mass spectrometry (LC-MS/MS) method was developed and validated for the determination of asiaticoside in beagle dog plasma. Plasma samples were extracted by protein precipitation with methanol. The chromatographic separation was performed on a C18 column with the isocratic mobile phase comprising of 78% methanol in water and 10 mM ammonium acetate buffer. Asiaticoside and the IS were detected with a triple-quadrupole tandem mass spectrometer in the negative ion mode for drug quantification. The total analytical run time was relatively short (4 min), and the limit of assay quantification (LLOQ) was 2.4 ng/mL using 300 μL of dog plasma. Asiaticoside and the internal standard (nimodipine) were monitored in the multi-reaction-monitoring (MRM) mode as follows: m/z 957.4→469.4 and m/z 417.2→122.0, respectively. The standard curve was linear over a concentration range from 2 to 190 ng/mL, and the correlation coefficients were greater than 0.998. The recoveries of asiaticoside from plasma were larger than 81.7%, and RSD of inter-day and intra-day assay were below 8.2%. The validated method was firstly applied to investigate the pharmacokinetics of asiaticoside in dogs.
Keywords: Electrospray ionization